Psychoanalysis, the good life, and human development - Harcourt, E (Johns Hopkins University Press, 2018)
In my paper I focused on the ‘dual roles claim’, the claim that some concepts central to at least certain versions of psychoanalysis classify people in respect both of their degree of mental health and of their degree of psychological maturity. I argued that no concept can be expected to play both roles, and that the real point of these particular psychoanalytic concepts is first and foremost to do neither, but rather to draw ethical distinctions. Groarke in his reply is concerned with that claim of mine, but perhaps more concerned with a corollary of it, which I stated but didn't argue for, namely that psychoanalysis is, in part, continuous with moral philosophy. The fact that I didn't argue for that second claim, or indeed set it out very fully, may perhaps explain why it sometimes feels as if we are talking at cross purposes. In my paper I focused on the ‘dual roles claim’, the claim that some concepts central to at least certain versions of psychoanalysis classify people in respect both of their degree of mental health and of their degree of psychological maturity. I argued that no concept can be expected to play both roles, and that the real point of these particular psychoanalytic concepts is first and foremost to do neither, but rather to draw ethical distinctions. Groarke in his reply is concerned with that claim of mine, but perhaps more concerned with a corollary of it, which I stated but didn't argue for, namely that psychoanalysis is, in part, continuous with moral philosophy. The fact that I didn't argue for that second claim, or indeed set it out very fully, may perhaps explain why it sometimes feels as if we are talking at cross purposes.